2019
DOI: 10.1590/0100-3984.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT with 99mTc-sestamibi for the evaluation of skeletal muscle perfusion after electrical muscle stimulation in athletes

Abstract: Objective: The purpose of this study was to evaluate the effects of electrical muscle stimulation (EMS) on muscles, using 99mTc-sestamibi SPECT/CT. Materials and Methods: We prospectively enrolled 20 consecutive male professional water polo players. The mean age was 25 years (range, 18-36 years). All athletes underwent 99mTc-sestamibi SPECT/CT of the thigh (rectus femoris and vastus medialis muscle groups) before and after EMS. Images were quantified to identify increases in perfusion after EMS. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A number of recent studies conducted in Brazil have emphasized the importance of nuclear medicine, especially 18 F-FDG-PET/CT, for the diagnosis and follow-up of various illnesses (14)(15)(16)(17)(18) . The present study showed how 18 F-FDG-PET/CT can aid clinicians during the decisionmaking process in cases of SPN with an intermediate probability of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies conducted in Brazil have emphasized the importance of nuclear medicine, especially 18 F-FDG-PET/CT, for the diagnosis and follow-up of various illnesses (14)(15)(16)(17)(18) . The present study showed how 18 F-FDG-PET/CT can aid clinicians during the decisionmaking process in cases of SPN with an intermediate probability of malignancy.…”
Section: Discussionmentioning
confidence: 99%